Amodiaquine as Topoisomerase I Inhibitors: A Computational Approach - Krishna, Rakki; Marimuthu, Karthikeyan (Asian Journal of Biological and Life Sciences, 2025)
Aim: The aim of this project is to utilize in silico approaches to identify potential anticancer agents by targeting the human topoisomerase I-DNA complex (PDB ID: 1A35), a critical enzyme involved in DNA replication and repair. The study focuses on evaluating the binding efficacy of repurposed drugs, including antifungal compounds, to expedite anticancer drug discovery. Materials and Methods: Protein Preparation: The 3D structure of the human topoisomerase I-DNA complex (PDB ID: 1A35) was retrieved, refined, and energy-minimized for molecular docking. Ligand Preparation: Irinotecan, Topotecan (known chemotherapeutics), and Amodiaquine (antifungal drug) were drawn in ChemDraw Ultra 8.0, converted to 3D structures, and energy-minimized using Chem3D Pro 8.0. Drug-Likeness Screening: Ligands were assessed via Lipinski’s Rule of Five to evaluate pharmacokinetic suitability. Molecular Docking: AutoDock Vina in PyRx was employed for docking ligands to the protein. Binding interactions were visualized using Biovia Discovery Studio 2024 Client. Results: Docking scores revealed binding energies of -8.4 kcal/ mol for Irinotecan, -7.6 kcal/mol for Topotecan, and -7.0 kcal/mol for Amodiaquine. Amodiaquine demonstrated stable interactions with key residues of topoisomerase I, suggesting potential inhibition of DNA-enzyme complexes. All ligands adhered to Lipinski’s Rule of Five, confirming favorable drug-like properties. Conclusion: This in silico study highlights Amodiaquine as a promising repurposed candidate for anticancer therapy, with notable binding affinity and interactions with topoisomerase I. While Irinotecan exhibited the strongest binding, Amodiaquine’s efficacy underscores the potential of antifungal drugs in oncology. Further in vitro and in vivo validation is warranted to confirm its therapeutic utility.
Keywords: Amodiaquine; Anticancer agents; AutoDock Vina; in silico study; Lipinski’s Rule of Five; Molecular docking; Topoisomerase I